Incidence of Cancer and Premalignant Lesions in Surgical Specimens of Transgender Patients. Issue 1 (24th December 2020) - Jacoby, Adam; Rifkin, William; Zhao, Lee C.; Bluebond-Langner, Rachel
Abstract : Background: Gender-affirming surgery is becoming increasingly more common. Procedures including chest masculinization, breast augmentation, vaginoplasty, metoidioplasty, and phalloplasty routinely generate discarded tissue. The incidence of finding an occult malignancy or premalignant lesion in specimens from gender-affirming surgery is unknown. The authors therefore conducted a retrospective review of all transgender patients at their institution who underwent gender-affirming surgery to determine the incidence of precancerous and malignant lesions found incidentally. Methods: A retrospective review of transgender patients who underwent gender-affirming surgery at the authors' institution between 2017 and 2018 performed by a single plastic surgeon and a single reconstructive urologic surgeon was conducted. Only transgender patients who underwent gender-affirming surgery that led to routine pathologic review of discarded tissue (mastectomy, vaginoplasty, vaginectomy as part of phalloplasty) were included. Charts were reviewed and patient demographics, duration of hormonal therapy, medical comorbidities, genetic risk factors for cancer, medications (including steroids or other immunosuppressants), pathology reports, and cancer management were recorded. Results: Between 2017 and 2018, 295 transgender patients underwent gender-affirming surgery that generated discarded tissue sent for pathologic evaluation. During this period, 193 bilateral mastectomies, 94 vaginoplasties with orchiectomies, and eight vaginectomies were performed; 6.4 percent of all patients had an atypical lesion found on routine pathologic evaluation. Conclusions: Gender-affirming surgery is increasingly more common given the increase in access to care. The authors' review of routine pathologic specimens generated from gender-affirming surgery yielded a 6.4 percent rate of finding atypical lesions requiring further evaluation. The authors advocate that all specimens be sent for pathologic evaluation.